Hole-Doping Induced Ferromagnetism in Monolayer SnO: A First-Principles Study. (16th August 2017) - Houssa, Michel; Iordanidou, Konstantina; Pourtois, Geoffrey; Afanas'ev, Valery V; Stesmans, Andre
Abstract : Hole-doping of monolayer SnO, which should result in a stable ferromagnetic order in this two-dimensional material, is theoretically studied, using first-principles simulations, based on density functional theory. Sn vacancies are predicted to behave like acceptors and to produce a spin-polarized gap state near the valence band edge. The formation energy of these defects is relatively low, especially under oxygen-rich growth conditions. Extrinsic doping of monolayer SnO is next investigated. It is found that the substitution of tin by indium as well as the substitution of oxygen by nitrogen should result in p-type doping of the material.